The Influence of Competence and Career Development on Employee Performance with Work Motivation as an Intervening Variable - Hamdan, Hamdan; Gemina, Dwi; Yuningsih, Erni; Samsuri, Samsuri; Ismartaya, Ismartaya (Universitas Respati Indonesia, 2023)
Competition in the automotive industry requires companies to manage human resources in order to drive business growth and compete to win market share. This study aims to determine the direct effect and indirect effect, competence and career development on employee performance through work motivation employees through work motivation. Population in this study is Yamaha JG Motor Bogor employees consisting of 49 people. Sampling of 49 respondents was carried out by saturated sampling saturated. The data used in this study is ordinal data which is converted into interval-scale metric data with the method of successive interval. Data analysis using verification analysis, path analysis and sobel test analysis for intervening variables through the IBM SPSS program. The results showed that competence has a direct positive and significant effect on work motivation, while career development has no effect on work motivation. Competence has a direct positive significant on employee performance, and work motivation has a direct positive and significant effect on employee performance, while career development has no effect on employee performance. Competence has an indirect effect directly on employee performance through work motivation, while career development has no indirect effect on employee performance through work motivation. Keywords: Competence, Career Development, Work Motivation, Employee Performance